New Ru(II)/Os(II)-polypyridyl complexes for coupling to TiO2 surfaces through acetylacetone functionality and studies on interfacial electron-transfer dynamics - Banerjee, Tanmay; Biswas, Abul Kalam; Sahu, Tuhin Subhra; Ganguly, Bishwajit; Das, Amitava; Ghosh, Hirendra Nath (Dalton Transactions, 2014)
New Ru(II)- and Os(II)-polypyridyl complexes have been synthesized with pendant acetylacetone (acac) functionality for anchoring on nanoparticulate TiO2 surfaces with a goal of developing an alternate sensitizer that could be utilized for designing an efficient dye-sensitized solar cell (DSSC). Time-resolved transient absorption spectroscopic studies in the femtosecond time domain have been carried out. The charge recombination rates are observed to be very slow, compared with those for strongly coupled dye molecules having catechol as the anchoring functionality. The results of such studies reveal that electron-injection rates from the metal complex-based LUMO to the conduction band of TiO2 are faster than one would expect for an analogous complex in which the chromophoric core and the anchoring moiety are separated with multiple saturated C-C linkages. Such an observation is rationalized based on computational studies, and a relatively smaller spatial distance between the dye LUMO and the TiO2 surface accounted for this. Results of this study are compared with those for analogous complexes having a gem-dicarboxy group as the anchoring functionality for covalent binding to the TiO2 surface to compare the role of binding functionalities on electron-transfer dynamics.